(untitled) (Global Scientific Review, 2024)
Environmental degradation has emerged as an important global problem with serious consequences for human health. This research paper aims to explore the complex relationship between environmental degradation and its potential impact on human health. By comprehensively examining various aspects such as air pollution, water pollution, loss of biodiversity and climate change, this research aims to combat environmental degradation to promote healthy populations worldwide. emphasizes the necessity